Effects of a Probiotic Formulation on Seasonal Allergic Rhinitis in Adults—A Randomized Double-Blind Placebo-Controlled Trial: The Probiotics for Hay Fever Trial - Ried, Karin; Travica, Nikolaj; Paye, Yeah; Sali, Avni (Frontiers in Nutrition, 2022)
Background Seasonal-allergic-rhinitis (hayfever) affects about 4.6 million (20%) of Australians each year. Hayfever manifests as runny/blocked nose, and often itchy/sore/swollen eyes, with symptoms greatly impacting the quality-of-life. Rescue medication such as anti-histamines are often needed to restore function, but they may trigger some other unwanted side-effects. Probiotics have shown promise to reduce hayfever symptoms. In this randomised double-blind placebo-controlled 12-week trial we aimed to assess the tolerability and efficacy of the probiotic formula ‘NC-Seasonal-Biotic’ on symptoms, quality-of-life, and immunological and microbial factors. Methods Adults, who had previously suffered from hayfever symptoms, were screened for eligibility, and randomly allocated to probiotic or placebo trial-powder. Treatment effectiveness was assessed by questionnaires, the daily total-nasal-symptom-score, and the weekly rhinoconjunctivitis quality-of-life-questionnaire. Secondary outcome measures included immunological parameters such as T-cell immunity (Th1/Th2 ratio) and the stool-microbiome analysis. Tolerability was assessed weekly by the gastrointestinal-symptom-scale. Results Recruitment and follow-up were challenging around the 2020/21 hayfever season in Melbourne, Australia, due to the harsh Covid-19 restrictions and extended lockdowns. Out of the 82 adults enrolled in the study, 75% participated (n=60), and half (n=40) completed the 10-12-week intervention-period. In the intention-to-treat analysis, no significant differences in hayfever symptoms were apparent between the groups, while quality-of-life trended towards greater improvement in the active group. Intention-to-treat analysis was confounded due to a third of all participants not completing the full 10-12-week-intervention-period. Subgroup analyses of the participants (n=40) completing the full 10-12-week-study-period, revealed a significantly greater reduction in symptoms in the active-group compared to placebo, including runny-nose (p=0.04) and itchy-eyes (p=0.01). Furthermore, the active group reported significant improvements in the quality-of-life, including more functionality during the day (p=0.05), better sleep (p=0.005), less fatigue (p=0.04), less thirst (p=0.007), and less irritability (p=0.007). Immunological parameters, measured by T-helper cell ratio (Th1/Th2) improved significantly in the active group compared to placebo. Most microbial changes were not statistically different between the groups. The trial powder was generally well tolerated. Conclusions Our study suggests the probiotic formula ‘NC-Seasonal-Biotic’, taken for 10-12-weeks, to be effective in reducing hayfever symptoms, such as runny-nose and itchy-eyes, and improved the quality-of-life, and immunological parameters, while being well tolerated.